(Auto)biography and Authority: Dickens and Forster’s Reconstruction of a ‘National Treasure’ - Isabelle Hervouet-Farrar (Cahiers Victoriens et Edouardiens)
This paper considers the reconstruction by John Forster of Charles Dickens’s childhood through his use of what is usually called ‘the autobiographical fragment’, a short text dealing with the Blacking Warehouse episode which bears witness to both Dickens’s strict auto-censorship and his tendency to frenetic confession. That a revelation of intimate details might endanger the ‘national treasure’ that Dickens had become at the end of the forties (the phrase is borrowed from Jean Ferguson Carr) seems a good enough reason for Dickens to have abandoned the idea of writing his autobiography and to have given the piece to Forster. This paper first shows how Forster dealt with the fragment, its blanks, omissions and almost impressionistic structure in short scenes before revealing in his biography that the draft could be found almost verbatim in David Copperfield. Further, when it comes to the fragment, Dickens’s complex managerial stratagem proves to be an integral element in the reconstruction of his childhood experience. The question of authority is of course central, Dickens’s apparent lack of interest in the future publication of his text seeming particularly out of character in the light of the control he most certainly exerted over his friends, and more specifically his future biographer.